2008
DOI: 10.1186/1471-2407-8-100
|View full text |Cite
|
Sign up to set email alerts
|

Expression of estrogen receptor beta in the breast carcinoma of BRCA1 mutation carriers

Abstract: Background: Breast cancers (BC) in women carrying mutations in BRCA1 gene are more frequently estrogen receptor negative than the nonhereditary BC. Nevertheless, tamoxifen has been found to have a protective effect in preventing contralateral tumors in BRCA1 mutation carriers. The identification of the second human estrogen receptor, ERβ, raised a question of its role in hereditary breast cancer. The aim of this study was to assess the frequency of ERα, ERβ, PgR (progesterone receptor) and HER-2 expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 38 publications
3
20
1
4
Order By: Relevance
“…This is similar to 84% (94% BRCA1, 75% BRCA2 and 81% BRCAX) obtained by Daidone et al [19] and higher than 42% reported in a series of 48 patients with founder BRCA1 mutation [20]. Although potentially due to differing patient cohorts, the discrepancy with the latter study may be due to their use of a different polyclonal antibody.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…This is similar to 84% (94% BRCA1, 75% BRCA2 and 81% BRCAX) obtained by Daidone et al [19] and higher than 42% reported in a series of 48 patients with founder BRCA1 mutation [20]. Although potentially due to differing patient cohorts, the discrepancy with the latter study may be due to their use of a different polyclonal antibody.…”
Section: Discussioncontrasting
confidence: 50%
“…The first study in 44 familial cancer patients (16 BRCA1, 12 BRCA2 and 16 BRCAX) [19] and the second in 48 patients with BRCA1 founder mutation positive women [20]. However, there are no data regarding the range of expression for its different isoforms and the cellular pattern of expression for either BRCA1-or BRCA2-associated tumours.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that other mediators are involved in regulation of estrogen’s effects in these patients. Litwiniuk et al [46] examined ERα, ERβ and PR in 48 women with mutations in BRCA1 gene and in a control group of 120 breast cancer samples using antibodies for ERα, PR and ERβ. Their data revealed that only 14.5% of BRCA1-related cancers expressed ERα compared with 57.5% in the control group.…”
Section: Existence Of E2/erβ-mediated Signaling Pathways In Tn-brementioning
confidence: 99%
“…Mandusic et al [46] measured the expression of ERβ1 and ERβ5 mRNAs in the 60 breast cancer samples and correlated their expression with ERα and PR protein levels with clinical/histopathological parameters. They found an inverse correlation between ERβ5 expression and the levels of ERα and PR proteins in postmenopausal patients.…”
Section: Existence Of E2/erβ-mediated Signaling Pathways In Tn-brementioning
confidence: 99%
See 1 more Smart Citation